14 Principals Quality Assurance Mechanisms for Enhancing Quality Public Secondary Schools in Ese-Odo L.G.A of Ondo State - Ikuelogbon , Olamire; Anaenyeonu, Ifeoma .M.; Anaenyeonu, Ifeoma .M.; Eze, Grace Abiayo (International Journal of Educational Management, 2022)
This study ascertained principals’ quality assurance mechanisms for enhancing quality secondary schools in Ese-Odo LGA of Ondo State. Two research questions and one null hypothesis guided the study. The study adopted a descriptive survey research design. A sample of 60 made up of 20 principals and 40 were used for the study. The instrument used for data collection was a 30-item questionnaire. The research questions were answered using mean scores and standard deviations while the null hypothesis was tested using t-test statistics. The findings of the study revealed the mechanisms used by principals in assuring quality secondary schools. Also, it was revealed that principals’ quality assurance mechanisms used only assure quality public secondary schools to a little extent in the LGA. Based on the findings, the researchers recommended that principals should be fully committed in the implementation of experts prescribed quality assurance mechanisms and the Ministry of Education organizes seminars, workshops, conferences for principals where quality assurance mechanisms will be discussed for continuous quality improvement, among others.